The Role of Perceived Enjoyment on Motivating the Internet Use - Mujiyati, Mujiyati; Achyari, Didi (Benefit, 2008)
There are many advantage of the usage of internet, as new technology. Although there is anyoneis not willing to use it, it just caused by other factors wich influence it. According to perceivedenjoyment literature, as an intrinsic motivation and later also extrinsic motivation, it is importantfactor in motivating the usage of information system. Perceived enjoyment, with perceived usefulnessang perceived ease of use â in accordance to internet technology, will influence individual behavior inmotivating the usage of internet. Technology Acceptance amodel (TAM)Â theory indicates thatindividual acceptance toward the information system is motivated by their perception perceivedusefulnessand perceived ease of use that still need other variables to enlarge the understanding towardindividual behavior in motivating the usage of system, e.g. perceivedenjoyment.The purpose of this research is to test the role of perceived enjoyment, also perceived usefulnessand perceived ease of use, in motivating the usage internet. The sample of the research are 226respondents. The metode that is used to test hypothesis is by Structural Equation Modeling (SEM).The result of the research show that there is positif influence between perceived enjoymenttoward perceived usefulness and perceived ease of use in motivating the usage internet. Perceivedusefulness and perceived ease of use are not influent in motivating the usage of internet. The resul ofthe research also indicates that perceived enjoyment has an important role as an intrinsic motivation inthe usage of internet but perceived enjoyment is not influence positively in the usage of intrnet inwich it is mediated by perceived usefulness and perceived ease of use.